Modelling the critical determinants of architects’ work-related stress - Çivici, Tülay; Ayalp, Gulden Gumusburun (Taylor and Francis Ltd., 2024)
Architects wearing different hats simultaneously suffer from occupational stress due to different construction characteristics. Decreased productivity, excessive absenteeism, burnout, and turnover intention are all linked to the effects of occupational stress. This study aims to pinpoint the critical stressors experienced by architects within the Turkish construction sector. A systematic literature review was conducted, and a questionnaire incorporating 48 stress factors along with the Work Stress Scale was designed, employing the Job Demand Resource (JD–R) model as a guiding conceptual framework. The survey was conducted on design architects responsible for Turkey’s design process. In total, 320 fully completed questionnaires were returned. The critical stressors (CSs) were determined using normalized mean value analysis. The results revealed 37 CSs and six critical stress factors were identified by exploratory factor analysis. Further, a structural equation model (SEM) was built to critical determinants of architects’ stress. Financial deficiencies, changes in construction projects, and poor communication factors were the most critical determinants of architects’ work-related stress. Within this context, the findings offer two new and original determinants for work-related stress that differ from former studies. © 2024 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Architects; critical stress factors; stress; Turkish construction industry